PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA DENGAN SELF EFFICACY SEBAGAI VARIABEL PEMODERASI - Risakotta, Kathleen Asyera; Sapulette, Shella Gilby (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2023)
The purpose of this research is to find whether enterpreneuship education has an effect on Interest in enterpreneuship with Self efficacy as a moderating variable, and find whether the family environment influences interest in enterpreneuship with self efficacy as a moderating variable. This research was conducted with quantitative methodes. Sampling technique using purposive sampling. Primary data in the form of a questionnaire used in this study. This study uses the Moderated Regression Analysis (MRA). The results of the study show that enterpreneuship education influences the interest in enterpreneuship. The family environment influences the interest in enterpreneuship. Self efficacy moderate the relationship between enterpreneuship education dan enterpreneuship interest. Self efficacy moderates the relationship between the family environment and interest in enterpreneuship.